Be innovative and resilient: Empirical evidence from Saudi firms on how to translate entrepreneurial orientation into firm performance - Wassim J. Aloulou (Administrative Sciences, 2023)
This research seeks to investigate the relationship between entrepreneurial orientation dimensions (behavioral dimension EOBD and attitudinal dimension EOAD) and firm performance (FP) through a sequential mediation model of innovation capability (IC) and firm resilience capability (FRC) in a specific context. Sample data for this study were collected using a questionnaire survey from 225 randomly selected SMEs in Saudi Arabia and analyzed using structural equation modeling. The results revealed that there are significant relationships between EO dimensions and IC. No direct relationships were found between EO dimensions and FRC or between EOAD and FP. Therefore, IC plays a mediating role in the relationships between EO dimensions and FRC. In addition, FRC does not play a mediating role in the relationships between EO dimensions and FP. On the contrary, it plays a partial mediation between IC and FP. To our knowledge, little research has investigated simultaneously the effects of EO, IC, FRC and FP in the Saudi context. Our study contributes to the literature on entrepreneurship, innovation and resilience by providing new empirical evidence. It also contributes to managerial practices by displaying the importance of translating strategic EO dimensions into performance outcomes through IC and FRC.
Keywords: 350; entrepreneurial orientation; firm performance; firm resilience capability; innovation capability; Saudi Arabia